Effects of miR-103a-3p Targeted Regulation of TRIM66 Axis on Docetaxel Resistance and Glycolysis in Prostate Cancer Cells - Yi, Qiang; Wei, Junfeng; Li, Yangzhou (Frontiers in Genetics, 2022)
Objective: To study the expression of miR-103a-3p and TRIM66 in prostate cancer (PCa) cells and exploring the direct target genes of miR-103a-3p. To analyze the effects of miR-103a-3p targeted regulation of TRIM66 axis on docetaxel resistance and glycolysis of prostate cancer cells. Methods: Human normal prostate cells and PCa cells were purchased, the expressions of miR-103a-3p and TRIM66 were detected, and the relationship between miR-103a-3p and TRIM66 was analyzed. Docetaxel resistant (DR) PCa cells were established and transfected with miR-103a-3p and TRIM66 plasmid. MTT assay was used to detect cell viability, plate cloning assay was used to detect colony formation, wound healing assay was used to detect cell migration, and Transwell was used to detect cell invasion. Cell glycolysis was analyzed by cell glycolysis kit. Results: The expression of miR-103a-3p was low and TRIM66 was high in PCa cells; MiR-103a-3p had a binding site with TRIM66, and the double luciferase report confirmed that they had a targeting relationship; Compared with PCa group cells, DR group cells showed increased resistance to DTX, the resistance index was 13.33, and the doubling time of DR group cells was significantly longer than PCa group cells. DR group showed more obvious low expression of miR-103a-3p and high expression of TRIM66;After DR group cells were transfected with miR-103a-3p and TRIM66 plasmid, the expression of miR-103a-3p increased significantly and TRIM66 decreased significantly; Up regulation of miR-103a-3p and interference with TRIM66 can inhibit the proliferation, metastasis and glycolysis of DR cells. Conclusion: The expression of miR-103a-3p is down-regulated in the malignant progression of PCa and up-regulated of TRIM66 in the malignant progression of PCa, especially in DR resistance. Up regulation of miR-103a-3p and interference with TRIM66 can inhibit DR resistance and glycolysis of PCa cells. Targeting TRIM66 may provide potential application value for molecular therapy of prostate cancer.